Measuring Production Periodicity in a 5.56 mm Cartridge Case Manufacturing System Using Max-Plus Algebra - Wiwit Melinasari; Edy Sulistyadi; Ida Bagus Made Putra Jandhana; Suroto (Indonesian Journal of Advanced Research, 2026)
This study measures production periodicity in a 5.56 mm cartridge case manufacturing system using Max-Plus Algebra. The manufacturing system was modeled as a deterministic discrete event system consisting of eleven sequential stages, one lot of 20,000 units, and inter-process waiting time as a model parameter. A max-plus state-space model was formulated to capture temporal dependencies among stages, followed by eigenvalue analysis and iterative simulation in MATLAB. The results show a minimum production cycle time of 109.649 minutes, with the fire-hole drilling stage identified as the critical production stage. The model clarifies the stable production period of a pipeline manufacturing system and supports stage-focused production evaluation.